Relating Factors of Insomnia among Haemodialysis Patients - Kusuma, Henni; Ropyanto, Chandra Bagus; widyaningsih, susana; Sujianto, Untung (Nurse Media Journal of Nursing, 2018)
Background: Insomnia is a sleep disturbance which commonly occurs in haemodialysis patients. Some factors contribute to insomnia in dialysis patients such as demographic, biological, psychological, lifestyle, and dialysis factors. However, there are limited studies which investigate the relating factors of insomnia in haemodialysis patients in Indonesia.Purpose: This study aimed to analyze the relating factors of insomnia in haemodialysis patients in Semarang, Central Java, Indonesia.Methods: This study was a cross-sectional study which involved 102 samples recruited by consecutive sampling technique from two dialysis units in Semarang, Central Java. Data were collected by questionnaires and analyzed using Chi-square and multiple logistic regression to know the most relating factors of insomnia.Results: The result showed that insomnia occurred in 63 respondents (61.8%). Further analysis indicated that insomnia was related to anxiety (p=0.034, OR=2.36) and age (p=0.049; OR=1.75). There was no relationship between insomnia and the other factors such as gender, education level, occupation status, marital status, haemoglobin level, smoking and coffee consumption habit, and dialysis factor (period of dialysis). Moreover, anxiety was the most relating factors of insomnia among haemodyalsis patients.Conclusion: This study concluded that anxiety and age were independent factors related to insomnia. This study recommends that anxiety screening should be performed on haemodialysis Â patients. Anxiety in haemodialysis Â patients needs to be treated properly so that it will not develop into insomnia.